Atmega Microcontroller 2560 Based Safety System of Monitor Panel and Controller on a Small Excavator - Baharuddin, Randis; Hidayat, Taufik (Jurnal Rekayasa Mesin, 2020)
This study aimed to design and build an Atmega Microcontroller 2560 based safety system on a monitor panel and a controller on a small excavator. Atmega 2560 Microcontroller-based alarm technology is the right choice as a solution to prevent theft of monitor panels and controllers on small excavator units, using Passive Infra-Red (PIR) sensor number 1 in the cabin room, PIR sensor number 2 on the battery, and door switch that is between the cabin and the door, if there is theft in the cabin room, then the alarm will be active, if a theft occurs in the battery then the alarm will be active. The alarm indicator system uses a buzzer (horn) unit, and there is additional lighting in the cabin room with a 24V Light Emitting Diode (LED) lamp if the alarm is active. Using an alarm, the risk of losing the monitor panel and controller due to theft on the unit can be prevented. The study results showed that the tool could work appropriately according to the standard testing tool, PIR sensors number 1 and 2 could detect movement or radiation so that the alarm would be active for 15 seconds. The door switch was tested by looking at the alarm condition, if the cabin door were closed when it was in the locked position, the alarm would not be active, but if the door was locked and forcibly opened, then the alarm would be active continuously without stopping until the door was closed again.